Effect of Temperature Limits and Crop Density on Quality Characteristics of Oils and Fatty Acids in Regression Relationship with Soybean Yield - Alireza Alazmani; Masoumeh Naeemi; Abolfazl Faraji; Ali Rahemi Karizki; Leila Ahangar (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In order to investigate the effect of the growing day and plant density on some agronomic, morphophysiological and qualitative characteristics of the early-maturing line Soy-93-31 soybean, an experiment was conducted in the form of split plots in the form of a randomized complete block design in three replications. Two crop years 2017 and 2018 were implemented in Gorgan region. The first factor of growth days until harvest time includes five growth days (GDD) 2328, 2182, 1893, 1712 and 1499 resulting from the date of sowing (10, 24 June, 8, 12 July, 5 August) and the second factor is the distance between rows 24, 36 and 48 cm (42, 28 and 21 plants per square meter).in this experiment, grain yield, biological yield, number of pods per plant, number of seeds per pod, 1000 grain, oil yield, oil percentage and soybean fatty acids were measured. The results of this experiment showed that planting date and density had a significant effect on the percentage of soybean oil and fatty acids. The percentage of seed oil decreased with increasing planting time (delayed soybean) so that the highest percentage of soybean oil on 10 June and the lowest percentage of oil was obtained on 5 August. Also, based on the results of planting date and plant density had a significant effect on grain yield and grain yield components, the weight of 1000 soybeans decreased with delay in planting. With delay of sowing date in all densities, soybean grain yield decreased, so that the highest grain yield was observed on June 10 and the density of 42 plants per square meter (3760 kg.ha-1) and the lowest grain yield was observed. Soybean was obtained on August 5 and the density of 21 plants per square meter was (470 kg.ha-1). According to the results of this experiment, the planting date of 10 June and the density of 42 plants per square meter were the most desirable planting date and density to achieve maximum grain and oil yield.